The gastroprotective effects of canna edulis ker. tuber starch on peptic ulcer and the histopathological profile of rat stomach - Robby Najini; Moch Saiful Bachri; Sapto Yuliani (Universitas Ahmad Dahlan, 2018)
Ganyong rhizome (Canna edulis Ker.) empirically use for treating gastritis (peptic ulcers). Ganyong rhizome contains carbohydrates and flavonoid that can reduce inflammation in the gastric tissues and againsts free radicals that are contributing to the pathogenesis of peptic ulcers. This research aims to know the gastroprotective effect of ganyong rhizome on white female rats, Wistar strain, which were given alcohol (ethanol 96%) by dose 1 ml/200gBB and measuring the total flavonoids content in ganyong rhizome. This research is Post Test Only Control Group Design, using 30 rats, weight 150-200 g, age 6-8 weeks, health condition. It is divided into six groups. Group I (normal) were fed and watered only, Group II (control) were given a CMC-Na 0,5%, Group III-V were given a suspension of ganyong rhizome starch (SGRS) with each doses 250, 500, and 1000 mg/kgBB, then Group VI were given a sucralfate dose 360 mg/kgBB. Rats were given oral treatment for 14 days. An hour after the treatment on 14th day, the whole groups unless the group I were given ethanol 96% 1 ml/200gBB orally. Twenty four hours later the rats were sacrificed, dissected and taken its gastric for further analyzed the number of ulcers as well as the description of histopathology of the gastric. The results showed that ganyong rhizome starch can decrease the index ulcer and increase the protection ratio value to the control group with results of doses SGRS 250, 500, 1000 mg/kgBB sequentially i.e., 12,5; 50; and 75%. The description of histopathology also showed significant improvement of gastric tissue at a dose of 1000 mg/kgBB. In addition, on TLC-Densitometri test also obtained the total flavonoid compound in ganyong rhizome is 112,49 Â± 7,97 ppm. Conclusions of this research are that the ganyong rhizome positive contains flavonoid and it has gastroprotective effect by decreasing the number of index ulcer, increasing the protection ratio value, and improving the histopathology of gastric tissue which had given alcohol.